2015
DOI: 10.1021/acsami.5b01122
|View full text |Cite
|
Sign up to set email alerts
|

NiO Hierarchical Nanorings on SiC: Enhancing Relaxation to Tune Microwave Absorption at Elevated Temperature

Abstract: We fabricated NiO nanorings on SiC, a novel hierarchical architecture, by a facile two-step method. The dielectric properties depend on temperature and frequency in the range from 373 to 773 K and X band. The imaginary part and loss tangent increase more than four times and three times with increasing temperature, respectively. The architecture demonstrates multirelaxation and possesses high-efficient absorption. The reflection loss exceeds -40 dB and the bandwidth covers 85% of X band (approximately -20 dB). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
147
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(153 citation statements)
references
References 28 publications
(38 reference statements)
4
147
1
1
Order By: Relevance
“…40 In RGO/CeO 2 , CeO 2 particles randomly anchored on the RGO surface formed the hierarchical architecture; hence, the relaxation is dominant and induced by the multiple interfacial polarization in composites. 39 In addition, given the improved electric conductivity caused by the introduction of RGO, the enhanced complex permittivity of RGO/CeO 2 is reasonable. 41 The relaxation and conductance of the composites may have a signi¯cant e®ect on the dielectric response of RGO/ CeO 2 .…”
Section: Em Parameters and Microwave Absorption Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…40 In RGO/CeO 2 , CeO 2 particles randomly anchored on the RGO surface formed the hierarchical architecture; hence, the relaxation is dominant and induced by the multiple interfacial polarization in composites. 39 In addition, given the improved electric conductivity caused by the introduction of RGO, the enhanced complex permittivity of RGO/CeO 2 is reasonable. 41 The relaxation and conductance of the composites may have a signi¯cant e®ect on the dielectric response of RGO/ CeO 2 .…”
Section: Em Parameters and Microwave Absorption Propertiesmentioning
confidence: 97%
“…The signi¯cant°uctuations that appear in the curve of real and imaginary permittivity of composites in the range of 2-18 GHz are attributed to the multiple interfacial polarization in composites because of the hierarchical architecture. 11,39 The " 00 of RGO/CeO 2 is signi¯cantly higher than that of pure CeO 2 , and " 00 indicates the evidence of relaxation. According to Debye theory, the imaginary part, " 00 , could be regarded as the complex contributions of both relaxation and conductance.…”
Section: Em Parameters and Microwave Absorption Propertiesmentioning
confidence: 99%
“…Over the past decades, ferrite absorbers [35], ferroelectric materials [6, 7], conductive polymers [810], and composite materials [11, 12] have been researched, but the traditional microwave-absorbing materials cannot meet all of the requirements such as strong absorption, wide range of absorption frequency, thin thickness, and light weight at the same time [13]. The previous reports have demonstrated that incorporating magnetic particles and dielectric material achieves great enhancement in microwave absorption properties [1418]. …”
Section: Introductionmentioning
confidence: 99%
“…Relaxation I, was located at the frequencies of 7.1, 9.4, and 13.5 GHz for raw Cryp, 1-Co-Cryp, and 2-Co-Cryp, respectively. The relaxation of Cryp was mainly from interfacial polarization and defect dipole polarization394546. As the Co(III) doping increased, the frequency of relaxation I shifted to higher frequencies.…”
Section: Resultsmentioning
confidence: 97%